Pengembangan Media Pembelajaran Daring Materi Sistem Pernapasan Manusia Untuk Pebelajar Sekolah Menengah Pertama - Erni Nidatul Dwi Utari; Sulton Sulton; Eka Pramono Adi (JKTP: Jurnal Kajian Teknologi Pendidikan, 2021)
This study has the aim of developing a product in the form of online learning media using moodle on the human respiratory system material that is feasible and valid for the learning of VIII grade junior high school students. Online learning media using Moodle is integrated as an online learning medium that can be accessed by students via the web anywhere and anytime, so that it can attract students' motivation to learn independently. This study uses the development model of Lee and Owens (2004). The results of the media expert validation obtained a percentage value of 95% and the material expert validation obtained a percentage of 100%. While the results of the student feasibility test obtained a percentage of 97.5%. Based on these results, online learning media using moodle is valid and suitable for students to use for independent learning. The use of learning media is a solution for educators to deliver online learning to make it easier and more structured and helps students increase their enthusiasm for learning at home.AbstrakPenelitian ini memiliki tujuan mengembangkan produk berupa media pembelajaran daring menggunakan moodle pada materi sistem pernapasan manusia yang layak dan valid digunakan untuk pembelajaran pebelajar kelas VIII SMP. Media pembelajaran daring menggunakan moodle diintegrasikan sebagai media belajar online yang dapat diakses pebelajar melalui web dimanapun dan kapanpun, sehingga dapat menarik motivasi pebelajar untuk belajar secara mandiri. Pada penelitian ini menggunakan model pengembangan Lee dan Owens (2004). Hasil dari validasi ahli media memperoleh persentase nilai sebesar 95% dan validasi ahli materi memperoleh persentase sebesar nilai 100%. Sedangkan hasil uji kelayakan pebelajar memperoleh persentase sebesar 97,5%. Berdasarkan hasil tersebut media pembelajaran daring menggunakan moodle valid serta layak digunakan pebelajar belajar mandiri. Penggunaan media pembelajaran tersebut menjadi solusi bagi pendidik untuk menyampaikan pembelajaran dengan online agar lebih mudah dan terstuktur serta membantu pebelajar meningkatkan semangat belajar di rumah.